2022
DOI: 10.3390/metabo12010044
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Alaska Pollock Protein Attenuates the Experimental Colitis Induced by Dextran Sulfate Sodium via Regulation of Gut Microbiota and Its Metabolites in Mice

Abstract: Protein derived from fish has not only nutritional properties but also health-promoting properties. Few studies have examined the effect of dietary Alaska pollock protein (APP) on the anticolitis effect reported to be associated with metabolic syndrome (MetS). This study investigated the effect of APP intake on colitis symptoms, gut microbiota, and its metabolites in the experimental colitis mouse model induced by dextran sulfate sodium (DSS). Male C57BL/6J mice were divided into three groups: (1) DSS-untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In a study by Tanaka et al . (2022), APP suppressed the reduction of the Simpson index in C57BL/6J mice as an effect of dextran sulfate sodium (DSS) theraphy. They also reported that APP reduces the F/B ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Tanaka et al . (2022), APP suppressed the reduction of the Simpson index in C57BL/6J mice as an effect of dextran sulfate sodium (DSS) theraphy. They also reported that APP reduces the F/B ratio.…”
Section: Resultsmentioning
confidence: 99%
“…APP's biological activities including skeletal muscle hypertrophy (Mizushige et al, 2010;Kawabata et al, 2015;Watanabe et al, 2018Watanabe et al, , 2020Watanabe et al, , 2021Fujitani et al, 2019;Morisasa et al, 2019Morisasa et al, , 2022Uchida et al, 2022), anti-obesity (Oishi & Dohmoto, 2009;Mizushige et al, 2017;Maedaa et al, 2020), gut microbiota composition regulation (Hosomi et al, 2020;Maedaa et al, 2020;Tanaka et al, 2022), anti-cholesterol (Shukla et al, 2006;Hosomi et al, 2009Hosomi et al, , 2010Hosomi et al, , 2011Kato et al, 2011;Maedaa et al, 2020), blood glucose lowering (Oishi & Dohmoto, 2009;Kawabata et al, 2015;Hosomi et al, 2020) and non-alcoholic fatty liver disease (NAFLD; Shukla et al, 2006;Hosomi et al, 2009;Maedaa et al, 2020) have been reported. Although research on APP's biological activities have been conducted, there are no systematic reviews as per our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Mass microorganisms in the intestinal tract make up the intestinal flora, where Firmicutes and Bacteroides are recognized as among the most prevalent phyla, and the ratio of F/B is indicative of inflammation . An enhanced F/B ratio was observed by Tanaka et al in a colitis mouse model established with DSS, and the intestinal flora dysregulation featured the increase of Proteobacteria . Likewise, Guo et al indicated the increase of Proteobacteria in UC patients.…”
Section: Discussionmentioning
confidence: 97%
“…Expression levels of tumor necrosis factor ( Tnf ) α, interleukin ( Il ) 1β , and Il6 in the mucosa of the distal colon were measured by quantitative PCR, as described in our previous report [ 21 ].…”
Section: Methodsmentioning
confidence: 99%